STRATEGI PENCARIAN SENYAWA BIOAKTIF BARU DARI SUMBER BAHAN ALAMI TUMBUHAN - Partomuan Simanjuntak (JURNAL ILMU KEFARMASIAN INDONESIA, 2003)
Plants provide enormous chemical diversity. Advances in bioassay screening, isolation techniques and structural elucidation have shortened and facilited the process of drug discovery from Indonesian medicinal plants. It is now general practice among natural product chemist and others field to use some strateg: for investigate bioactive compounds from natural product.